APPLICATION OF SERVQUAL AND QUALITY FUNCTION DEPLOYMENT METHODS IN EFFORTS TO IMPROVE ACADEMIC SERVICES BY LECTURERS - Noya, Sunday; Han’s, Steven; Purnomo (Fakultas Ekonomi, Universitas Negeri Jakarta, 2023)
This research was conducted to measure the level of academic quality in the services provided by instructors at the Faculty of Science and Technology (FST) at XYZ University. The Servqual method was employed to assess the factors influencing the academic service quality of instructors, Importance Performance Analysis was used to identify these factors, and Quality Function Deployment (QFD) was utilized to propose improvements for enhancing academic service quality. The research sample consisted of students and the FST management. The Servqual method involved analyzing GAP 5 and GAP 1, revealing numerous attributes with negative values, indicating a lack of student satisfaction, and identifying discrepancies between management perceptions and student expectations. The Importance Performance Analysis yielded 9 attributes that were prioritized for improvement. Subsequently, using QFD, 8 technical responses were identified as recommended improvements by management to enhance the quality of academic services.